2002
DOI: 10.1262/jrd.48.205
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Transgenes in Rats: The Contributions of Embryo Cryopreservation and Intracytoplasmic Sperm/Spermatid Injection.

Abstract: Abstract. The maintenance of transgenes in rats is reviewed with special references to embryo cryopreservation (transgene banking) and intracytoplasmic injection of spermatozoa or round spermatids (transgene passage). Production of transgenic rats by pronuclear DNA microinjection is easily performed, particularly using the micro-vibration method. Two-cell stage embryos derived from the mating of transgenic rats with wild-type rats can be successfully cryopreserved by conventional two-step freezing in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Pregnancy rates of foster mothers after embryo transfer of intact or microinjected zygotes were not different. The proportion of microinjected zygotes resulting in live offspring was ranging from 16.7 to 38.7% and was thus comparable to corresponding literature data (Charreau et al, 1996;Hirabayashi et al, 2001a;Hochi & Hirabayashi, 2002;Kato et al, 2004b). Surprisingly, full-term development of microinjected zygotes of the LEW strain transferred to foster mothers was higher compared to the other strains.…”
Section: Overall Efficiency Of Transgenesissupporting
confidence: 86%
See 1 more Smart Citation
“…Pregnancy rates of foster mothers after embryo transfer of intact or microinjected zygotes were not different. The proportion of microinjected zygotes resulting in live offspring was ranging from 16.7 to 38.7% and was thus comparable to corresponding literature data (Charreau et al, 1996;Hirabayashi et al, 2001a;Hochi & Hirabayashi, 2002;Kato et al, 2004b). Surprisingly, full-term development of microinjected zygotes of the LEW strain transferred to foster mothers was higher compared to the other strains.…”
Section: Overall Efficiency Of Transgenesissupporting
confidence: 86%
“…The most important one is the skill of the scientist performing microinjections. It is known that pronuclear microinjection in rats is relative difficult compared to the mouse and there seems to be a 'knack' in microinjecting exogenous DNA solution into the pronucleus of rat zygotes (Hochi & Hirabayashi, 2002). In addition, the purification techniques of DNA for injection, the DNA concentration, the method used for microinjection and other factors are also very important for the outcome of transgenic technology (Wall, 2001).…”
Section: Overall Efficiency Of Transgenesismentioning
confidence: 99%
“…Moreover, the low rate of full-term development after ROSI [61] may be explained either by the abnormal pattern of paternal genome demethylation [36] or by the abnormal localization of methylated chromatin in the nucleoplasm of male pronucleus rather than the failure to completely demethylate the paternal genome [38]. On the other hand, in vitro production of rat zygotes is not efficient as in mouse, despite of the successful birth of ICSI-or ROSI-derived rat offspring [62]. Paternal genome active demethylation in IVF-and ICSI-derived rat zygotes occurred at a similar timing (6 to 10 h after fertilization), but to lesser extent compared to the in vivo-derived counterparts.…”
Section: Effect Of In Vitro Embryo Production On Active Demethylationmentioning
confidence: 99%
“…Isotani et al [33] recently reported that rat ES cells injected into nu/nu mouse blastocysts could contribute to form not only thymus but also sperm-like germ cells. Although the minimal essential techniques for microinsemination, such as intracytoplasmic sperm injection and round spermatid injection, are almost available in the rat [34], the functional normality of the rat germ celllike cells observed in such xenogenic chimeras has not yet been confirmed. Nevertheless, the interspecies blastocyst complementation system using mutant mice or experimentally nitch-induced mice and pluripotent stem cells of the rats would provide an appropriate model for generation of human germ cells in the body of non-human species.…”
Section: Organ Regeneration By Blastocyst Complementationmentioning
confidence: 99%